To find the equation of the parabola given the points from the table, we can use the general form of a quadratic equation:
\[ y = ax^2 + bx + c \]
We have four points to consider:
- (-1, -7)
- (1, 13)
- (3, -7)
- (5, -67)
Since there are three coefficients \(a\), \(b\), and \(c\), we can derive three equations from three of the points, and then we can test for a fourth point to ensure our solution is correct.
Let's use the first three points. We can set up the following equations:
-
From (-1, -7): \[ -7 = a(-1)^2 + b(-1) + c \implies -7 = a - b + c \quad (1) \]
-
From (1, 13): \[ 13 = a(1)^2 + b(1) + c \implies 13 = a + b + c \quad (2) \]
-
From (3, -7): \[ -7 = a(3)^2 + b(3) + c \implies -7 = 9a + 3b + c \quad (3) \]
We now have three equations:
- \( a - b + c = -7 \)
- \( a + b + c = 13 \)
- \( 9a + 3b + c = -7 \)
Now let's solve this system of equations:
Step 1: Subtract equations (1) from (2): \[ (a + b + c) - (a - b + c) = 13 + 7 \implies 2b = 20 \implies b = 10 \]
Step 2: Substitute \(b = 10\) into equations (1) and (2):
Substituting into (1): \[ a - 10 + c = -7 \implies a + c = 3 \quad (4) \]
Substituting into (2): \[ a + 10 + c = 13 \implies a + c = 3 \quad (5) \]
Both (4) and (5) are consistent as they yield the same result. We now substitute \(b = 10\) into (3):
\[ 9a + 3(10) + c = -7 \implies 9a + 30 + c = -7 \]
Rearranging this gives us: \[ 9a + c = -37 \quad (6) \]
Now we can solve for \(a\) using equations (4) and (6). From equation (4), we know: \[ c = 3 - a \]
Substituting this into equation (6): \[ 9a + (3 - a) = -37 \implies 9a - a + 3 = -37 \implies 8a + 3 = -37 \implies 8a = -40 \implies a = -5 \]
Now substituting \(a = -5\) back to find \(c\): \[ c = 3 - (-5) = 3 + 5 = 8 \]
So we have:
- \(a = -5\)
- \(b = 10\)
- \(c = 8\)
Thus, the equation of the parabola is: \[ y = -5x^2 + 10x + 8 \]
This is the equation whose graph is a parabola that fits the points in the table.